(untitled) - Shapiro, Stephen M. (Hoboken, N.J., 2006)
A counter-intuitive and simple guide for creating a passion-filled life. In this competitive world, we're always running around trying to meet the next big goal. But often we forget to enjoy life every day, and instead wait for some imagined future in which we'll finally allow ourselves to live the life we really want. Goal-Free Living presents a new philosophy for life-that we can achieve the extraordinary life we've always dreamed of now rather than later, and we can achieve it without goals or a play-by-play handbook. Rather than let society, parents, or expectations define their aspirations, people who live goal-free lives are driven by their passion. This book shares the personal discovery of author Stephen Shapiro, who followed his goals until he was extremely successful-and entirely miserable. Based on his interviews with hundreds of individuals from a multitude of backgrounds-a powerful business executive, a Hollywood television producer, a sports psychology consultant-this book shows exhausted professionals and goalaholics everywhere how to stop being slaves to their goals and create a life they love based on experiential living. Shapiro distills the art of goal-free living down to nine basic secrets that can free anyone from the tyranny of their goals. He explains why being goal-oriented isn't the best way to get ahead at work, how goals can de-motivate people, how goal obsession affects every aspect of life, and how goals can stifle creativity and adaptability. Packed with true stories of ordinary people and their extraordinary lives, Goal-Free Living shows everyone how to be successful on their own terms without missing out on the one thing we only get one shot at-life. Stephen M. Shapiro (Quincy, MA) is an expert and professional speaker on the topics of creativity and innovation. He is the founder of The 24/7 Innovation Group, a management education and research organization focused on innovation and breakthrough thinking. He formerly worked at Accenture, where he led their Process Excellence Practice.
Keywords: Lifestyles,Quality of life,Lối sống,Chất lượng cuộc sống